ANTROPOLOGI KEKERASAN AGAMA : Studi Pemikiran Jack David Eller - Rohmawati Rohmawati (Sabda: Jurnal Kajian Kebudayaan, 2018)
This article aims to study the anthropology of religious violence in Jack David Eller's perspective. The conclusions are: (1) violence, anthropologically, is not an objective quality of a concept and a judgment, depending on the person who sees it. Some violence is considered good and ordered as rights and obligations; (2) the factors supporting violence are: constituents of cultural violence, integration into groups, identities, institutions, interests, and ideologies; (3) religious violence is practiced in all religions because there are some aspects of violence in religious doctrine; (4) religious violence has various forms: sacrifice, martyrdom, persecution, holy war, ethno-religious conflict, abuse, crime and murder.